MODERNISASI BIROKRASI DIGITAL: ANALISIS IMPLEMENTASI APLIKASI MOBILE JKN SEBAGAI INOVASI KEBIJAKAN BPJS KESEHATAN - Fattiha Syanira Nirmala Amantha; Shella Sofiana; Syarifah Noor Aliya; Charren Galuh; Shandy Gupa Pratama; Aqil Teguh Fathani (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the implementation of the Mobile JKN application as a policy innovation by BPJS Kesehatan in supporting the modernization of healthcare service bureaucracy at Gatot Soebroto Army Central Hospital (RSPAD Gatot Soebroto). The study employed a qualitative method with a descriptive approach through in-depth interviews, observations, and document analysis involving patients and hospital administrative staff. The findings indicate that the implementation of Mobile JKN has improved service efficiency by reducing waiting times, simplifying administrative procedures, and strengthening a more integrated service system. For users, the application facilitates access to healthcare services through digital registration and online queue features, while for service providers it enhances operational efficiency and data management accuracy. However, its implementation remains constrained by limited digital literacy, inadequate device availability, technical issues, and initial user resistance. Therefore, the success of digital transformation requires strengthened human resource capacity, improved technological infrastructure, and continuous public education.